Similarity Property and Slide Attack of Block Cipher FESH - Yafei Zheng; Wenling Wu (IET Information Security)
This paper focuses on similarity properties and extension of the classical slide property of block ciphers. Taking FESH, an award-winning block cipher of the National Cryptographic Algorithm Design Competition 2019, as an example, similarity properties of the encryption and key transformation are found, owing to the similar structures that the encryption and key transformation adopted, and the constants generation. Based on the similarity properties, extended slide properties can be constructed for FESH. Slide attacks of FESH are then proposed. The similarity properties and extended slide property are immune to the increasing of iterated rounds, i.e., it cannot be avoided by increasing the round number of FESH. Furthermore, extended slide property helps relaxing the strict requirements of the subkeys in slide attacks. Taking Feistel and SPN structures as examples, frameworks of slide attacks based on the extended slide properties are presented. Slide attack of FESH is exactly a concrete example of SPN structure.